Permeation fill-tube design for inertial confinement fusion target capsules. (22nd March 2017) - Rice, B.S.; Ulreich, J.; Fella, C.; Crippen, J.; Fitzsimmons, P.; Nikroo, A.
Abstract : A unique approach for permeation filling of nonpermeable inertial confinement fusion target capsules with deuterium–tritium (DT) is presented. This process uses a permeable capsule coupled into the final target capsule with a 0.03-mm-diameter fill tube. Leak free permeation filling of glow-discharge polymerization (GDP) targets using this method have been successfully demonstrated, as well as ice layering of the target, yielding an inner ice surface roughness of 1- $\unicode[STIX]{x03BC}$ m rms (root mean square). Finally, the measured DT ice-thickness profile for this experiment was used to validate a thermal model's prediction of the same thickness profile.